2021
DOI: 10.22437/irje.v5i1.12187
|View full text |Cite
|
Sign up to set email alerts
|

Socio-Constructivist Learning and Teacher Education Students’ Conceptual Understanding and Attitude toward Fractions

Abstract: The study assessed the conceptual understanding and attitude toward fractions of teacher education students in a socio-constructivist learning environment. Specifically, it determined the students’ level of conceptual understanding before and after instruction; verified the types of conceptual changes that occurred; and ascertained the attitude of students toward fractions before and after instruction and its relationship to their levels of understanding. Descriptive-correlational research method was used. Soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 14 publications
1
19
3
Order By: Relevance
“…Most (40 out of 45) PMTs recorded their best conceptual understanding in problem-solving (Table 3). This shows that the PMTs have prior knowledge of the concepts and mastered the skills needed in problem-solving, which opposes the work of Ibañez and Pentang (2021) and Pentang et al (2021) who revealed that the majority of the preservice teachers have functional misconceptions and an incomplete understanding of problem-solving. This result approves the effective use of Google Classroom with the Khan Academy as employed by the PMTs' professors where the institution they belong to has led to the standard of being one of the best universities in Asia.…”
Section: Pmts' Level Of Conceptual Understandingcontrasting
confidence: 56%
See 2 more Smart Citations
“…Most (40 out of 45) PMTs recorded their best conceptual understanding in problem-solving (Table 3). This shows that the PMTs have prior knowledge of the concepts and mastered the skills needed in problem-solving, which opposes the work of Ibañez and Pentang (2021) and Pentang et al (2021) who revealed that the majority of the preservice teachers have functional misconceptions and an incomplete understanding of problem-solving. This result approves the effective use of Google Classroom with the Khan Academy as employed by the PMTs' professors where the institution they belong to has led to the standard of being one of the best universities in Asia.…”
Section: Pmts' Level Of Conceptual Understandingcontrasting
confidence: 56%
“…Poor conceptual understanding may also be a product of a negative mindset. Ibañez and Pentang (2021) have reported this among preservice teachers in the Philippines. Discovering ways to develop a strong mindset and conceptual understanding among PMTs was disrupted by the occurrence of the novel coronavirus disease in 2019 .…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…This is consistent with the findings of previous studies. Separate studies by Consuegra et al (2016), Gustavsen (2019) and Ibañez and Pentang (2021) found that if a student's peer group represents a vibrant and active group that always actively participates in school and class activities, the student would be socialised to be active and to participate actively in school and class activities, and vice versa. In his study, Nusche (2015) also found that the levels of interaction of students in the classroom depend on their perceptions of how they are perceived by their peers.…”
Section: Discussionmentioning
confidence: 99%
“…However, two components of the philosophy of teaching in early childhood education can be distinguished (Fischer et al, 2020;Copple & Bredekamp, 2009). These are the teacher's cognitive processes and thought structures, such as planning, interactive decision-making, and reflection; the knowledge, beliefs, and attitudes are stored as schemas in the teacher's mind (Ibañez & Pentang, 2021). The divide between the fluid processes and semipermanent structures of the mind echoes Schwab's (1961) difference between the syntax and semantics of a field, as well as the conventional philosophical dichotomy between structure and functions (Philp & Goyen, 1973).…”
Section: Introductionmentioning
confidence: 99%